Economic analysis of the provision of industrial and manufacturing services in the Kingdom of Saudi Arab 2024 - Al-Shuwaikhat, Sadiq Ali Mubarak; Al Tuwaym, Haya Ibrahim Abdulrahman; Al-Dawsari, Sara Saad (Journal of Economic, Administrative and Legal Sciences, 2025)
The Kingdom is one of the largest economic countries in the Middle East, as it is believed to be witnessing a major economic transformation at the beginning of 2018, which is the beginning of its vision for 2030, which is a strategic vision to achieve diversity in sources of income in the Kingdom and diversity in the industrial field and to reach it to raise local production and rely on it to a greater extent, where the provision of services comes. In an effective and advanced manner, it constitutes a major impetus for strengthening the industrial and manufacturing sectors in the country. This is why the current research studied the analysis of the economic impact of providing services on the industrial and manufacturing sectors in the Kingdom. This is by arriving at an answer to the main question: How does the provision of advanced services contribute to enhancing the economic performance of the industrial and manufacturing sectors in the Kingdom? Saudi Arab?,  This is done through the use of the descriptive analytical approach, which focuses on examining the theoretical foundations related to the subject through reviewing relevant Arab and foreign references. In addition to carrying out a field study, which consists of distributing questionnaires to different categories of the selected sample, in order to reach an answer to the basic research problem, and this is through the final results of the research that were reached, which are as follows: There is a high level of provision of transport and communication services in industrial companies and the industrial and manufacturing sector. In the Kingdom of Saudi Arabia from the point of view of the study sample members, the arithmetic mean value was 4.121 with a standard deviation of 0.800., In addition to Saudi Arabia from the point of view of the study sample members, where the arithmetic mean value was 4.304 with a standard deviation of 0.694. The following research recommended the necessity of strengthening the digital and technological infrastructure in the industrial and manufacturing areas in the Kingdom to improve the quality of services provided.
Keywords: economic impact; services; industrial sector; manufacturing